2020
DOI: 10.2147/cmar.s238513
|View full text |Cite
|
Sign up to set email alerts
|

<p>Circ-ABCB10 Contributes to Paclitaxel Resistance in Breast Cancer Through Let-7a-5p/DUSP7 Axis</p>

Abstract: Background: Paclitaxel (PTX) is one of the widely used chemotherapy drugs in breast cancer (BC) treatment. Unfortunately, the survival rate of metastatic BC patients remains poor due to PTX resistance. Therefore, uncovering the underlying mechanism behind the PTX resistance of BC cells is crucial for BC therapy. Methods: The enrichment of circular RNA ATP binding cassette subfamily B member 10 (circ-ABCB10), let-7a-5p and dual specificity phosphatase 7 (DUSP7) was measured by quantitative real time polymerase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 27 publications
2
54
0
1
Order By: Relevance
“…CircRNAs are transcripts that are closed covalently and are resistant to exoribonuclease degradation, which are usually more stable than linear transcripts [5]. Aberrant circRNA expression has been discovered in many kinds of cancers such as breast [6], colorectal [7], gastric [8], and lung [9]. For prostate cancer, studies show that circLMTK2 acts as tumor suppressor in PCa through regulating microRNA-183 expression [10].…”
Section: Introductionmentioning
confidence: 99%
“…CircRNAs are transcripts that are closed covalently and are resistant to exoribonuclease degradation, which are usually more stable than linear transcripts [5]. Aberrant circRNA expression has been discovered in many kinds of cancers such as breast [6], colorectal [7], gastric [8], and lung [9]. For prostate cancer, studies show that circLMTK2 acts as tumor suppressor in PCa through regulating microRNA-183 expression [10].…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer has been a major public health problem worldwide among women ( 1 3 ), and thus breast cancer research has an important social significance. Recently, many related studies have shown that circ_RNF111 and circ_ABCB10 contribute to paclitaxel resistance in breast cancer ( 40 , 41 ), circ_ZEB1 acts as an oncogene in triple-negative breast cancer ( 42 ), circ_TFF1 contributes to breast cancer progression ( 43 ), circ_0000526 blocks the progression of breast cancer ( 44 ), circulating circ_RNA hsa_circ_0001785 acts as a diagnostic biomarker for breast cancer ( 45 ), etc. In the present study, the major focus was on BLBC molecular subtype, and protooncogene circ_NOTCH3 was first identified to act as a sponge for miR-205-5p, which played a crucial role in its development and progression.…”
Section: Discussionmentioning
confidence: 99%
“…Low expression levels of miR-7 have long been proven to confer resistance to breast cancer chemotherapy [127]. In another study of ADM-resistant breast cancer, circKDM4C downregulation was found to inhibit tumour progression and alleviate ADM resistance by regulating the miR-548p/PBLD axis [128]. Additionally, the expression level of circMTO1 (hsa_circ_007874) in monastrol-resistant breast cancer cell lines is significantly reduced compared with that in monastrol-sensitive breast cancer cell lines, and overexpression of circMTO1 can reverse monastrol resistance through the circRNA/TNF receptor-associated factor 4 (TRAF4)/Eg5 pathway [129].…”
Section: Breast Cancermentioning
confidence: 99%